Exploring escape room for learners engagement - Nordin, Azlin (2024)
Escape rooms, traditionally designed for entertainment, have found a surprising niche in higher education, particularly in fields like software engineering. They offer a hands-on, immersive, and collaborative learning experience that can significantly enhance student engagement and understanding. Escape rooms have been shown to significantly boost student engagement and motivation. In programming courses, students preferred these interactive activities over traditional laboratory sessions, highlighting the potential for escape rooms to create a more dynamic learning environment (López-Pernas et al., 2019). Similarly, in literature courses, escape rooms focused on human rights issues helped promote student ownership and civic engagement, demonstrating their versatility in various academic disciplines (Sendin, 2021).